TERIMALAH SATU AKAN YANG LAIN: Pendekatan Filosofis dan Teologis atas Otherness - Simanullang, Gonti (LOGOS, 2022)
Tolerance and the golden rule are taught by the world's religions, including the religions in Indonesia. The practice of tolerance and of the golden rule in multicultural Indonesian society is a real experience that needs to be improved. From the philosophical and theological point of view otherness must be accepted, recognized, appreciated, and enriched for the sake of a beautiful and peaceful common life in this world. In this article, the beauty of otherness is explored. The exploration tells us it is urgent to constantly promote the golden rule among adherents of different religions in Indonesia and the need for Catholics in Indonesia to be more precise in making real the adage 100% Catholic and 100% Indonesian.